ISLAMIC SPIRITUALITY-BASED GENDER COMMUNICATION: THEORETICAL AND CONTEXTUAL NARRATIVES - Pambayun, Ellys Lestari (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2025)
Intergender communication in Muslim societies is often influenced by social norms, patriarchal culture, and conservative religious interpretations, which can limit equality in speech, social roles, and leadership. This study focuses on how Islamic spirituality, which encompasses values such as tauhid (oneness of God), rahmah (compassion), adab (etiquette/morality), justice (keadilan), ihsan (excellence/sincerity), and sincere intention (niat ikhlas), can serve as a basis for forming a more just, empathetic, and transformative pattern of gender communication. Using the literature review method, this article collects relevant literature from classical and modern texts, as well as empirical research from Indonesian and global contexts. The narrative describes the framework of Islamic spirituality, analyzes the relationship between spirituality and gender communication, identifies challenges, and deepens the discussion on practical implications in the context of education, dakwah (Islamic preaching/outreach), media, and family. The results of the study indicate that Islamic spirituality offers the potential for the transformation of gender communication: through adab, moral equality before God, sincere intention, and sincere mutual respect between genders; however, obstacles such as patriarchal interpretations, local culture, regulatory uncertainty, and inadequate education are still very dominant. This study hopes to become a theoretical foundation for further empirical research and for communicative practices in Muslim communities that are more humane and spiritual.